Faktor yang Mempengaruhi Insiden Keselamatan Pasien di Ruang Rawat Inap RS X Depok Tahun 2024 - Kana, Merice Diana Novita; Oci Etri Nursanty; Risky Kusuma Hartono (2025)
Patient safety is a health service system that aims to prevent injuries and manage risks that can harm patients. Patient safety incidents have adverse impacts, including physical injuries. This study aims to describe patient safety incidents in the inpatient ward of RS X Depok. This study used a quantitative method with a cross-sectional design. The sample of the study was 61 nurses selected using a total sampling technique. The results showed that stress factors were related to adverse events (p = 0.046), while fatigue factors were related to sentinel events (p = 0.004). However, communication and manager leadership factors were not related to patient safety incidents. The conclusion of this study confirms that stress and fatigue are factors that contribute to patient safety incidents, while communication and manager leadership do not have a significant relationship. These results highlight the importance of managing stress and fatigue of health workers in improving patient safety in hospitals.